Menjalankan Kekuatan Eksekutorial Sertifikat Fidusia Terhadap Benda Jaminan oleh Ketua Pengadilan - Hefi Yudiyanto; Faisol Abrori (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The executorial power contained in the provisions of article 15 paragraph (2) of the Fiduciary Guarantee Law, makes the position of a fiduciary guarantee certificate equivalent to a court decision which has permanent legal force (inkracht van gewijsde). This executorial power is based on the mandate